HUBUNGAN PRAKTIK PEMBERIAN AIR SUSU IBU (ASI) DENGAN STATUS GIZI BAYI (USIA 0-6 BULAN) DI WILAYAH KERJA PUSKESMAS GAYAMSARI KOTA SEMARANG - Nadyah Ayu Ginanti; Dina Rahayuning Pangestuti; M. Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2017)
Breastfeeding practice is a great way to feed the most ideal for ages 4-6 months baby’s first since being born because breast milk can meet the infants nutritional needs with a balanced composition and customized baby growth. This research is done in the PuskesmasGayamsari working area which aims to know the correlation of  breastfeeding practice with infants nutritional status (age 0-6 months). the research design uses was cross sectional. The respondents in this research are breastfeeding mothers either exclusive or non exclusive who have babies aged 0-6 months as many as 42 people were devided into two groups, namely the group of exclusive breastfeeding and non exclusive breastfeeding. Samples are obtained by using purpossive sampling techniques. Data were collected by interview using a questionnaireand analyze with univariate and bivariate analysis. Bivariate analysis using fisher’s exact test, correlation product moment and independent sample T-test. Measurement result with anthropometry were measured using the index BB/U, PB/U and BB/PB shows that there is one baby (4,8%) are less nutrition in infants who had not given exclusive breastfeeding, one baby (4,8%) which were short on nutrients that babies not given exclusive breastfeeding, one baby (4,8%) were the skinny on nutrition of babies who were given exclusive breastfeeding and three babies (14,3%) skinny babies were not given exclusive breastfeeding.Statistical test result showed there is no correlation of breastfeeding practice and infants nutritional status (BB/U) (p=1,000), there is no correlation of breastfeeding practice and infants nutritional status (PB/U) (p=1,000), and no correlation of breastfeeding practice and infants nutritional status (BB/PB) (p=0,606). This research recommend that health care professional to provide knowledge of exclusive breastfeeding for breastfeeding mothers.